ERRATUM: Recommendations of Expert Group of Polish Society of Pediatric Oncology and Hematology on use of immune tolerance induction (ITI) in pediatric patients with hemophilia A complicated by a factor VIII inhibitor - Magdalena Wojdalska; Tomasz Urasiński; Paweł Łaguna; Anna Klukowska; Elżbieta Latos-Grazyńska; Irena Woźnica-Karczmarz; Danuta Pietrys; Andrzej Kołatan; Halina Bobrowska; Tomasz Szczepański; Wojciech Młynarski (Acta Haematologica Polonica)
This article presents recommendations developed by the Expert Group of the Polish Society of Pediatric Oncology and Hematology (PTOHD) for the use of immune tolerance induction (ITI) therapy in pediatric patients with hemophilia A (HA) complicated by the presence of factor VIII (FVIII) inhibitors. The presence of FVIII inhibitor is a serious complication of FVIII replacement therapy, requiring intensive monitoring and specific treatment. We have provided specific recommendations for monitoring FVIII inhibitor titer and its classification, as well as setting out the criteria for initiating and completing ITI. We describe different ITI regimens depending on the inhibitor titer and the management of breakthrough bleeding. We also highlight the importance of emicizumab administration in bleeding prophylaxis, and discuss different regimens for FVIII inhibitor eradication. This article discusses the criteria that define ITI efficacy as well as failure, and provides recommendations for the management of breakthrough bleeding during ITI. The aim of devising these recommendations was to optimize treatment and improve the quality of life of children with HA with inhibitors by providing them with the best possible medical care.